La investigación etnográfica en educación: análisis reconstructivo desde la semántica y la pragmática (Papeles, 2009)
This article reviews the ethnographic research method proposed by Phil Carspecken in his book Critical Ethnography in Educational Research; A Theoretical and Practical Guide. This ethnographic research method is framed in the qualitative critical research field in education. It allows us to establish a connection between the practice and theory in the analysis of our human interaction observations related to the structure of communication from three ontologic categories: subjective, objective and normative-evaluative.
Keywords: Meaning acts, inference, context, interpretation, horizons of semantic meaning, horizons of pragmatic meaning.